Annealing effect on the PCL mechanical, thermal and thermomechanical properties (Research, Society and Development, 2020)
Biodegradable polymers market has rapidly increased, and polycaprolactone (PCL) has arisen as interesting option for the polymer industry and the scientific community. The present work aimed to evaluate the annealing effect on mechanical (impact, tensile, flexural and hardness), thermomechanical (thermal deflection temperature (HDT) and Vicat softening temperature (VST)) and thermal properties (differential scanning calorimetry (DSC) and thermogravimetry (TG)) in PCL injected specimens. Elastic modulus, tensile strength, Shore D hardness, HDT, VST and thermal stability were improved after annealing at 50 °C; whereas impact strength and elongation at break decreased. Summing up, annealing improved PCL performance and can be considered as prosperous methodology to handle targeted properties for specific applications.